The costs and benefits of mercantilist warfare. (10th April 2018) - O'Brien, Patrick Karl
Abstract : This article offers an architectural blueprint for the study of economic connections between warfare in the early modern period and the long-term growth of Europe's competing national economies. It surveys and critically investigates the concepts derived mainly from economic theory and the statistical evidence accessible in primary and secondary sources for the investigation of this meta-problem for students of economic theory.